Efek Perbedaan Taraf Marinasi Ekstrak Kecombrang (Etlingera elatior) Terhadap Susut Masak dan Organoleptik Daging Kambing: Effect of Different Levels of Marination Kecombrang Extract (Etlingera elatior) on Cooking Loss and Organoleptics Goat Meat - Setyawati, Tyas; Utami, Efrilia Tri Wahyu (Fakultas Peternakan Universitas Jambi, 2024)
Background: Goat meat is a good medium for the growth and development of microorganisms due to its high nutrient content. Kecombrang is a type of plant that can be utilized by the community as a food preservative. Purpose: This study aims to test the value of cooking loss and organoleptic of marinated goat meat using kecombrang extract. Methods: The research design used in this study used a completely randomized design (CRD) with 4 treatments (addition of kecombrang extract of 0 ml = P0, 10 ml = P1, 20 ml = P2, 30 ml = P3) and 5 replications. Observation data were analyzed using analysis of variance (ANOVA) and significant data were contimued with Duncan’s Multiple Range Test (DMRT). Results: The result showed that cooking loss and organolepric goat meat added with marination of kecombrang extract with different levels of administration had significantly different results (p<0.05). Marination with kecombrang extract produced the highest cooking loss in the treatment of 20 ml, while the best organoleptic properties were obtained in the treatment of 30 ml kecombrang extract marination. Conclusion: Marination with kecombrang extract can significantly improve the cooking loss and organoleptic characteristics of goat meat.